The whirlpool algorithm based on physical phenomenon for solving optimization problems. Issue 2 (11th March 2019) - Zou, Yuanyang
Abstract : Purpose: This paper aims to propose a novel nature-inspired optimization algorithm, called whirlpool algorithm (WA), which imitates the physical phenomenon of whirlpool. Design/methodology/approach: The idea of this algorithm stems from the fact that the whirlpool has a descent direction and a vertex. Findings: WA is tested with two types of models: 29 typical mathematical optimization models and three engineering problems (tension/compression spring design, welded-beam design, pressure vessel design). Originality/value: The results shown that the WA is vying compared to the state-of-art algorithms likewise conservative approaches.